IDENTIFIKASI Vibrio sp PADA GONAD IKAN CAKALANG (Katsuwonus pelamis L) - Mewengkang, Hanny W (Sam Ratulangi University, 2010)
This research was conducted to identify the presence of Vibrio sp. at the gonads of fresh and smoked skipjack tuna. The method used in this research is descriptive method with the parameters examined, ie total bacteria, total Vibrio, morphology and biochemical tests. Results showed that the total value of Vibrio in fresh skipjack tuna gonad highest TVC 1.1x105/g and the lowest is 2.0x103 TVC/gr. While the smoke skipjack tuna gonad bacterial growth does not occur. The identification results found 43 strains of Vibrio sp., (7 strains), Vibrio fluvialis (2 strains), Vibrio cincinnatiensis (4 strains), Vibrio damsela (2 strains), Vibrio metschnikovii (1 strain) and 27 other strains was not identified.